The Zimbabwe Liberation War Veteran’s 1997 vetting process and its implications on former ZPRA Combatants. - Ngobe, Bhekuzulu L. (Midlands State University, 2017)
The study purports to trace the continuity in the history of the marginalization of former ZPRA combatants paying particular focus to the 1997 vetting process. This endeavor was stimulated by the various vetting exercises have been repeated time and again in which ZPRA veterans have clamored over being constantly sidelined by a system targeted at former ZPRA combatants. The research therefore traces back to the veteran policy shortcomingsof the post Second Chimurenga and how these transcended overto the twilight of the millennium in 1997 where some former ZPRA veterans were left out during the disbursement that would have contributed to their emancipation. It interrogates how the systems that were employed consciously and subconsciously side lined certain genuine veterans and benefitted manufactured veterans. Lastly the papers attempts at analyzing the implications of the manner in which events in the 1997 affected the standing of the war veterans and the general citizenry at a socio-political and economic level.The study employed the qualitative research approach that necessitated the interaction with the involved custodians of the vetting process of 1997 as well as the beneficiaries and the victims of the vetting process who proved that disenfranchisement of certain sections of the ZPRA veterans lay in the vetting criteria that not universal and inapplicable given the fundamental differences that lay in the composition of the former guerilla armies that is ZPRA and ZANLA and the manner in which they had been trained and operated during the liberation struggle.